Metabolic Engineering of Indole Glucosinolates in Chinese Cabbage Hairy Roots Expressing Arabidopsis CYP79B2, CYP79B3, and CYP83B1 - Zang, Yun-Xiang (Konkuk University, Seoul, Republic of Korea); Kim, D.H. (Konkuk University, Seoul, Republic of Korea), E-mail: kimdh@konkuk.ac.kr; Park, B.S. (National Institute of Agricultural Biotechnology, RDA, Suwon, Republic of Korea); Hong, S.B. (Konkuk University, Seoul, Republic of Korea), E-mail: dsbhong@konkuk.ac.kr (Biotechnology and bioprocess engineering, 2009)
Indole glucosinolates (IG), a group of secondary metabolites found almost extensively in the order Brassicales, play an important role in the interaction between plant and insect or microorganism. In order to explore the possibility of IG metabolic engineering in Chinese cabbage hairy roots, three Arabidopsis cDNAs CYP79B2, CYP79B3, and CYP83B1 combined with rolABC were introduced into Chinese cabbage by Agrobacterium-mediated transformation. Overexpression of CYP79B2, CYP79B3, or CYP83B1 alone did not affect the accumulation levels of IG in transgenic hairy roots. However, when CYP83B1 was overexpressed together with CYP79B2 and/or CYP79B3, some of the transgenic hairy roots accumulated higher levels of glucobrassicin. (GBC) or 4-methoxy glucobrassicin (4-OMeGBC) than control hairy root line carrying rolABC vector. With regard to the IG accumulation, overexpression of all three cDNAs showed no better than overexpression of both cDNAs. Both 4-OMeGBC and neoglucobrassicin (neo-GBC) were found to be the main components of IG that comprise about 90% of total IG in all types of Chinese cabbage hairy root lines. In transgenic hairy root lines rB3B1-8 and rB2B1B3-5, 4-OMeGBC increased to 2 and 1.5-fold, while neo-GBC decreased to 0.5 and 0.6-fold, respectively. This suggests that an increased production of 4-OMeGBC causes a reduction of neo-GBC level since the two types derive from a common precursor GBC. However, in terms of the total IG level, the transgenic hairy roots did not show significant differences from controls.